(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the predictive power of the Lipid Accumulation Products (LAP) index in the identification of cardiovascular risk in patients with kidney disease undergoing hemodialysis compared to traditional anthropometric and biochemical indicators. Methods: cross-sectional study involving 77 patients with Chronic Kidney Disease (CKD) undergoing hemodialysis treatment. Identification data, anthropometry and biochemical measurements were collected. Anthropometric, biochemical and combination of both (LAP) indicators were calculated. A receiver operating characteristic (ROC) curve was performed and the areas under the curve were estimated in order to identify the power of identification of Cardiovascular Risk (CVR) and establish cutoff points for the indicators. Results: Most individuals presented cardiovascular risk according to the Waist-Height Ratio (WHR). Medians of total cholesterol and triglycerides and mean LDL-c were higher in the CVR group assessed by non-HDL cholesterol compared to those without CVR (p<0.05). The LAP score showed significant differences between the CVR groups, with the LAP median being 77.54 (45.72-142.88), higher in the group with CVR compared to those without CVR, 43.06 (30.98- 77.06). LAP (AUC: 0.705; 95%CI: 0.589-0.821; p=0.003) was the best discriminator of RCV, where LAP cutoff point >92.21, sensitivity of 44% and specificity of 92.59% were estimated to identify the RCV. Conclusion: The LAP index showed greater power in identifying the CVR when compared to isolated anthropometric or biochemical measurements.